Asuhan Keperawatan Keluarga Tn. B dengan Gangguan Sistem Kardiovaskular: Hipertensi Pada Ny. J di Desa Kalibuntu RT 05 RW 02 Kecamatan Losari Kabupate Brebes - Taufikurrokhman Taufikurrokhman; Esti Nur Janah; Siti Fatimah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Hypertension is a condition where blood pressure is higher than the normal limit, namely for systolic ≥140 mmHg and for diastolic ≥90 mmHg. The purpose of this writing is to find out and provide nursing care for Mr. B’s family with cardiovascular system disorders: hypertension in Mr. J in Kalibuntu Village Rt 05 Rw 02 Losari District Brebes Regency according to nursing standards. The method used s the data collection method in the form of interviews, observations, documentation studies and physical examinations. From the case rewiew, it was found that the client’s main complaint was pain in the back of the head and pain in the neck, P: pain increases during activity, Q: pain like being cut, R: pain in the back of the head, S: pain scale 4 (moderate), T: pain comes and goes. The nursing problems found were acute pain and knowledge deficit. Interventions are arranged based on the theory in SDKI, SLKI and SIKI as well as on the client’s condition and can be implemented.